2000
DOI: 10.1007/s002149900062
|View full text |Cite
|
Sign up to set email alerts
|

The influence of protecting the hydroxyl group of β-oxy-α-diazo carbonyl compounds in the competition between Wolff rearrangement and [1,2]-hydrogen shift. Density functional theory study and topological analysis of the charge density

Abstract: The in¯uence of protecting the hydroxyl group of a b-oxy-a-diazo carbonyl compound on the competition between the Wol rearrangement (WR) and the [1,2]-hydrogen shift (HS) was investigated theoretically. Stationary points on the potential-energy surface were located with the B3LYP density functional and the 6-31G** basis set. For the basic system geometry optimisations at B3LYP/6-311+G** were performed to validate the reliability of the B3LYP/6-31G** calculations. Singlepoint energy calculations were carried ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2010
2010

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…[85] In some cases where Wolff rearrangement can compete with 1,2-H shift, namely in the case of an -oxy--ketocarbene, the use of water as solvent can even suppress the Wolff rearrangement product formation to exclusively yield 1,2-H migration product. [86,87] Recently, it was shown that the contribution from a free carbene to the alkene formation, which changes with the nature of the substituents, ranges from 60 % (R= Me) to 100 % (R=H) for the cases studied, however a dependence on the irradiation wavelength was observed. [88] In regarding to the migratory aptitudes of the substituents, the same trend described for the Wolff rearrangement was observed, since the migratory ability of a substituent is an inherent characteristic.…”
Section: Scheme 21mentioning
confidence: 91%
“…[85] In some cases where Wolff rearrangement can compete with 1,2-H shift, namely in the case of an -oxy--ketocarbene, the use of water as solvent can even suppress the Wolff rearrangement product formation to exclusively yield 1,2-H migration product. [86,87] Recently, it was shown that the contribution from a free carbene to the alkene formation, which changes with the nature of the substituents, ranges from 60 % (R= Me) to 100 % (R=H) for the cases studied, however a dependence on the irradiation wavelength was observed. [88] In regarding to the migratory aptitudes of the substituents, the same trend described for the Wolff rearrangement was observed, since the migratory ability of a substituent is an inherent characteristic.…”
Section: Scheme 21mentioning
confidence: 91%